To the question of teaching students productive writing in the foreign language - Alla A. Rybkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The problem of teaching students productive writing is considered. Russian teachers and methodologists understand the purposes and problems of training students differently, making various demands to the result of productive writing. In the article the analysis of theoretical views on a problem of training students is offered. In the course of formation of skills of written language the author suggests to be guided not only by a letter product - the text, but also by process of creation of written speech work, and also pays attention to various approaches to the theory of estimation of written works of students with the different level of language competence. Recurrence of nature of process of the letter makes the training of students in various methods of editing written works logical. Lag in the level of writing skills in a foreign language can be overcome on condition of different use of the exercises which are based on the modern principles of training in foreign languages.